Analisis Tingkat Kecemasan Pasca Cedera pada Pemain Futsal Putra Universitas Negeri Surabaya - Danielle Batistuta Kunarto; Abdul Aziz Hakim; Pudjijuniarto Pudjijuniarto; Made Pramono; Anna Noordia (Pusat riset dan Inovasi Nasional, 2025)
Sports are an important physical activity to engage in, but they can also lead to issues such as injuries, particularly for futsal players. The risk of injury is higher in sports that involve physical contact with opponents, such as futsal, and athletes who have experienced injuries may experience anxiety. This research used a cross-sectional design and a descriptive research methodology. The sample consisted of 18 respondents obtained through purposive sampling. Data analysis techniques used descriptive percentages. The results of the study showed that the anxiety levels of the respondents were categorized as “very low” 0 (0%), “low” 7 players (39%), “moderate” 3 players (16%), ‘high’ 7 players (39%), and “very high” 1 player (6%). Based on the average value of “27.11,” the anxiety level of UNESA futsal players falls into the “moderate” category. The injury levels of the respondents were as follows: “Level 1 injury” for 5 respondents (28%), “Level 2 injury” for 11 respondents (61%), and “Level 3 injury” for 2 respondents (11%). The injury levels of the respondents were categorized as “Level 2 Injury.” The conclusion of this study is categorized as “Moderate” with a percentage of 27.11%.